2011
DOI: 10.1007/s10725-011-9614-x
|View full text |Cite
|
Sign up to set email alerts
|

UV-B radiation induces changes in polyamine metabolism in the red seaweed Porphyra cinnamomea

Abstract: Early investigations on the productivity of intertidal seaweeds found that, unlike some seaweeds, members of the genus Porphyra, a Rhodophyte, could tolerate physical stressors such as ultraviolet-B radiation (UV-B) both during immersion and when exposed to air. Increased stress tolerance was thought to be due to an unknown mechanism that operated at the thylakoid level. As recent research has shown that polyamines (PAs), bound to the thylakoid membranes of chloroplasts, play a critical role in protecting the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 56 publications
1
18
0
Order By: Relevance
“…) under UV‐B stress showed a significant increase in PA levels and in ADC activity (Schweikert et al. ). In this study, we clearly demonstrate that these changes are due to a switch to increased PUT synthesis via the ADC pathway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…) under UV‐B stress showed a significant increase in PA levels and in ADC activity (Schweikert et al. ). In this study, we clearly demonstrate that these changes are due to a switch to increased PUT synthesis via the ADC pathway.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, the activity of both PUT synthesizing enzymes, ADC and ODC, increased (Schweikert et al. ). Exposure of the cyanobacteria Synechocystis to osmotic stress resulted in decreased ADC activity and SPD levels, whereas PUT levels stayed at control levels (Jantaro et al.…”
mentioning
confidence: 99%
“…, Schweikert et al. ). It has also been shown that macroalgae can synthesize PUT via the ODC and the ADC pathways (Lee , Sacramento et al.…”
Section: Polyamines Present In Macroalgaementioning
confidence: 99%
“…, Schweikert et al. ). PA levels in the thalli of macroalgae under salinity stress vary greatly (Lee ).…”
Section: Functions Of Polyaminesmentioning
confidence: 99%
“…Their involvement in acclimation processes of PSII such as the down regulation of antenna size, increases in nonphotochemical quenching and ROS scavenging during light stress suggest important photoprotective roles (Groppa & Benavides, 2008;Ioannidis et al, 2011). For macroalgae, the involvement of polyamines in UV stress responses has been examined in very few studies indicating that UV-B exposure can increase the amounts of polyamines (mainly PUT) up to 200% as reported for the red alga Porphyra cinnamomea (Schweikert et al, 2011). The action mechanism of polyamines in macroalgae remains unclear, but some evidence suggests that these molecules bind to other compounds (e.g.…”
Section: Polyaminesmentioning
confidence: 99%